Performance of Green Roofs on Building Energy Efficiency in Tropical and Subtropical Climates - Saleh, Muhammad; Fitriaty, Puteri; Bassaleng, Andi Jiba Rifai (Technium Social Sciences Journal, 2025)
This research examines the performance of green roof architectural designs in enhancing energy efficiency in buildings within tropical and subtropical climates. Green roofs, which integrate vegetation and planting media, can improve energy efficiency by reducing the heat absorbed by buildings, thereby increasing indoor thermal comfort and lowering the need for air conditioning. The study employs a comparative method to analyse the performance of green roofs in improving energy efficiency across both climates. From 218 selected searches, 15 studies indicate that both intensive and extensive green roofs can reduce the surface temperature of concrete roofs through vegetation evapotranspiration, leading to decreased energy consumption, particularly for air conditioning.